Islamic ethical governance: An integrated model for corruption prevention - Abdurrahman, Zahron (Nur Science Institute, 2025)
This study develops an integrated Islamic Ethical Governance model for organizational corruption prevention, incorporating Islamic values of 'adl (justice), amanah (trust), shura (consultation), and Islamic business ethics. Using a qualitative systematic literature review approach, relevant scholarly sources were analyzed through thematic coding to create a conceptual framework integrating modern governance principles with Islamic ethical values. The research presents a comprehensive four-element model: 'adl-based internal and external control mechanisms promoting justice; amanah-driven transparency and accountability reflecting moral responsibility; shura-institutionalized ethical training and participatory consultation fostering anti-corruption values; and Islamic business ethics implementing socially responsible behavior through CSR rooted in maslahah, ihsan, and taqwa. This holistic framework provides a foundation for nurturing anti-corruption organizational behavior. It contributes a theoretically grounded, practically applicable framework for implementing Islamic ethical governance as a sustainable anti-corruption strategy, addressing existing literature gaps in corruption prevention mechanisms.